CO2-Driven Hydraulic Fracturing Trajectories across a Preexisting Fracture. (29th April 2021) - Zhang, Qi; Wang, Jiehao; Gao, Yufeng; Cao, Shengfei; Xie, Jingli; Ma, Like; Liu, Yuemiao
Abstract : Defining the trajectory of hydraulic fractures crossing bedding planes and other fractures is a significant issue in determining the effectiveness of the stimulation. In this work, a damage evolution law is used to describe the initiation and propagation of the fracture. The model couples rock deformation and gas seepage using the finite element method and is validated against classical theoretical analysis. The simulation results define four basic intersection scenarios between the fluid-driven and preexisting fractures: (a) inserting—the hydraulic fracture inserts into a bedding plane and continues to propagate along it; (b) L-shaped crossing—the hydraulic fracture approaches the fracture/bedding plane then branches into the plane without crossing it; (c) T-shaped crossing—the hydraulic fracture approaches the fracture/bedding plane, branches into it, and crosses through it; (d) direct crossing—the hydraulic fracture crosses one or more bedding planes without branching into them. The intersection scenario changes from (a) → (b) → (c) → (d) in specimens with horizontal bedding planes when the stress ratio β (β = σ y / σ x ) increases from 0.2 to 5. Similarly, the intersection type changes from (d) → (c) → (a) with an increase in the bedding plane angle α (0° → 90°). Stiffness of the bedding planes also exerts a significant influence on the propagation of hydraulic fractures. As the stiffness ratio E 1 ¯ / E 2 ¯ increases from 0.1 to 0.4 and 0.8, the seepage area decreases from 22.2% to 41.8%, and the intersection type changes from a T-shaped crossing to a direct crossing.